Establishing First Age-Friendly Health System Tele-Palliative Care Clinic – Facilitators, Challenges, Lessons Learned to Improve Care for Rural, Older Veterans. - Hartz, Stephanie; Garbin, Alexander; McGuire, Courtney; Steagall, Jill; McCauliff, Jocelyn; Nearing, Kathryn Allen (Inquiry (00469580), 2025)
Age Friendly Health Systems (AFHS) promote geriatric best practices to improve healthcare quality, minimize harms and support older adults' care preferences. AFHS-designated clinics consistently address the Geriatric 4Ms: Mentation, Mobility, Medication, and What Matters Most. The VA Eastern Colorado Health Care System tele-Palliative Care clinic achieved AFHS Level 1 and 2 recognition in 2021, becoming the first AFHS-designated telemedicine clinic in the nation. An interprofessional team and older Veterans guided planning and implementation. Using existing staff and clinic workflows, we consistently addressed the Geriatric 4Ms during visits. Specific metrics include: (1) AFHS Level 1 and 2 recognition, (2) maintenance in addressing Geriatric 4Ms in tele-Palliative Care, (3) number of patients served, (4) travel-miles saved. FY23-24, we conducted 192 AFHS tele-Palliative Care visits, 81% with rural/highly rural Veterans. We served 108 unique patients (FY23:57; FY24:51; percent decrease = 10.5%). Compared to Colorado's Veteran population, Veterans from racial/ethnic minority backgrounds and women were underrepresented; older Veterans were overrepresented. In FY23/FY24, the majority of patients were White (82%/73%), not Hispanic/Latino (83%/73%), male (100%/98%), and ≥65 (90%/89%). All 4Ms were addressed for 86% (FY23) and 76% (FY24) of unique patients. AFHS tele-Palliative Care saved Veterans/caregivers 23 622 (FY23) and 18 632 (FY24) miles of travel. Congruent with AFHS, Palliative Care focuses on physical, emotional, and psychosocial aspects of serious illness. AFHS designation in a tele-Palliative Care clinic is novel nationally. We demonstrated that evidence-based care can be provided to every older adult, regardless of care modality, without expanding staff or changing clinical workflows.